Investigating nutrient requirements of grouper fish for feed formulation - Soong, Cai Juan; Ramli, Razamin; Abd Rahman, Rosshairy (Universiti Teknikal Malaysia Melaka, 2016)
High nutrients and desirable taste of grouper fish affect the high demand in grouper fish in the current prevailing market.Nevertheless, , wild catch grouper fish in current prevailing market supply is limited and insufficient to meet the cyclical nature of high demand in grouper fish consumption leading to the high price.For that reason, grouper fish is worth farming.Hence, there is a need to formulate the fish feed since it is important to have correct nutrients requirement for feed formulation to ensure the adequacy of the diet for the grouper fish.Therefore, the aim of this study is to investigate the proper range of nutrients need in the fish feed.Data was collected from 30 manufacturers of grouper fish feed meal and analysis were done by SPSS. Quantitative analysis includes descriptive statistics, coefficient of variance, one sample test, pearson analysis and correlation were used for analysing nutrients data.Results show that grouper fish require seven approximate nutrients that are crude protein 40-45%, crude fat 1-10%, crude fibre 0.5-8%, moisture 0.8-95.5%, ash 0.4-18%, phosphorus 0.1-1.8%, calcium 2-4%, and nine essential amino acids (EAA) which are Arginine 2.06-4.21%, Histidine 0.66-1.26%, Isoleucine 1.2-2.57%, leucine 2.23-4.23%, lysine 1.96-4.04%, methionine 0.89-1.81%, Phenylalanine 0.89-2.46%, Threonine 1.29-2.59% and Valine1.46-2.86%. This vital information can be counted in such a further study in fish feed formulation to reduce cost and maximize profitability in grouper fish farming.